2013
DOI: 10.1515/ling-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

The social and linguistic in the acquisition of sociolinguistic norms: Caregivers, children, and variation

Abstract: Despite the assumption in early studies that children are monostylistic until sometime around adolescence, a number of studies since then have demonstrated that adult-like patterns of variation may be acquired much earlier. How much earlier, however, is still subject to some debate. In this paper we contribute to this research through an analysis of a number of lexical, phonological and morphosyntactic variables across 29 caregiver/child pairs aged 2;10 to 4;2 in interaction with their primary caregivers. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 30 publications
1
80
0
1
Order By: Relevance
“…Labov, 1964;Roberts, 1994;Roberts, 1997a;Roberts & Labov, 1995;Kerswill, 1996;Chambers, 1992Chambers, , 2002Foulkes, Docherty & Watt, 2005;Smith, Durham & Fortune, 2007;Tagliamonte & Molfenter, 2007;Smith, Durham & Richards, 2013). Some studies have examined the pattern of acquisition of sociolinguistic variation by children (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Labov, 1964;Roberts, 1994;Roberts, 1997a;Roberts & Labov, 1995;Kerswill, 1996;Chambers, 1992Chambers, , 2002Foulkes, Docherty & Watt, 2005;Smith, Durham & Fortune, 2007;Tagliamonte & Molfenter, 2007;Smith, Durham & Richards, 2013). Some studies have examined the pattern of acquisition of sociolinguistic variation by children (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the pattern of acquisition of sociolinguistic variation by children (e.g. Smith et al 2007;Smith et al 2013) as well as the order in which social and linguistic constraints are acquired (e.g. Labov, 1989;Roberts, 1994;Tagliamonte & A previous study (Habib, 2017) compared the use of the variable (q) (realized as the rural uvular voiceless stop [q] or urban glottal stop [ʔ]) in the speech of the same parents and children and showed that although children do not acquire the frequencies that exist in their immediate environment, they acquire the linguistic gender differences in their community; boys, like men, use the rural form [q] much more than girls.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations